2013
DOI: 10.5603/ep.2013.0010
|View full text |Cite
|
Sign up to set email alerts
|

Dunnigan-type familial partial lipodystrophy associated with the heterozygous R482W mutation in LMNA gene — case study of three women from one family

Abstract: Lipodystrophies are a heterogeneous group of diseases affecting adipose tissue distribution. Familial partial lipodystrophy of the Dunnigan type (FPLD) is a rare autosomal, dominant disorder caused by missense mutations in lamin A/C (LMNA) gene where selective loss of subcutaneous adipose tissue from the limbs and trunk, and accumulation of fat in the neck and face, is usually associated with a variety of metabolic disorders including insulin resistance, diabetes mellitus, dyslipidemia, hepatic steatosis and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…We present a case of a 24 year old Caucasian female diagnosed with FPLD at the age 21 based on physical examination, positive family history (her mother and sister were diagnosed with FLPD) and genetic studies. Direct DNA sequencing revealed a heterozygous missense mutation at codon 482 (c.1444C>T; R482W) located in exon 8 of the LMNA gene what was described in detail elsewhere [4]. Since diagnosis she has been treated with multiple daily injections (MDIs) of insulin analogue (insulin aspart before meals and insulin detemir at night) and 3000 mg of metformin.…”
Section: Case Presentationmentioning
confidence: 89%
“…We present a case of a 24 year old Caucasian female diagnosed with FPLD at the age 21 based on physical examination, positive family history (her mother and sister were diagnosed with FLPD) and genetic studies. Direct DNA sequencing revealed a heterozygous missense mutation at codon 482 (c.1444C>T; R482W) located in exon 8 of the LMNA gene what was described in detail elsewhere [4]. Since diagnosis she has been treated with multiple daily injections (MDIs) of insulin analogue (insulin aspart before meals and insulin detemir at night) and 3000 mg of metformin.…”
Section: Case Presentationmentioning
confidence: 89%
“…Lack of fertility and obstetrical complications are frequent with FPLD2. Vantyghem et al reported a prevalence of polycystic ovarian syndrome of more than 50%, of infertility close to 30%, miscarriages of 50%, gestational diabetes of at least 30%, and preeclampsia and foetal death of over 10% [ 25 , 32 ]. Contrary to these previous reports, our patient had no history of polycystic ovarian syndrome, nor any signs of hyperandrogenism, and presented no difficulties in conceiving.…”
Section: Discussionmentioning
confidence: 99%
“…The mutant gene products may disrupt interaction with chromatin or other nuclear lamina proteins, resulting in abnormal differentiation and the premature death of adipocytes [ 17 - 19 ]. Most mutations cluster in the carboxy-terminal immunoglobulin domain of lamin A/C [ 3 ], and the majority of patients have heterozygous missense mutations, affecting codon 482 on exon 8 [ 20 - 25 ]. FPLD2 patients are born with normal fat distribution and after puberty they lose subcutaneous fat from their extremities, trunk and gluteal regions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the recent findings relating LMNA mutations to the fibro‐fatty replacement typical of ARVC, the connection among aberrant lamins and adipose tissues had already been widely investigated over the years, as in the case of Dunnigan type familial partial lipodystrophy. Nowadays it is well‐known that the majority of LMNA mutations causing FPLD leads to aminoacid substitutions within the immunoglobulin‐type domain of lamin A/C (Nabrdalik et al, ), and the LMNA R482W mutation is the most frequent genotype related to familial partial lipodystrophy of the Dunnigan type (Vantyghem et al, ).…”
Section: Lamins In Health and Diseasementioning
confidence: 99%
“…Nowadays it is well-known that the majority of LMNA mutations causing FPLD leads to aminoacid substitutions within the immunoglobulintype domain of lamin A/C (Nabrdalik et al, 2013), and the LMNA R482W mutation is the most frequent genotype related to familial partial lipodystrophy of the Dunnigan type (Vantyghem et al, 2004).…”
Section: Pathological Conditions Associated To Laminsmentioning
confidence: 99%